The Concentration of Manganese, Copper, Zinc, Lead and Thorium in Sediments of Paka Estuary,Terengganu, Malaysia - B. Y., Kamaruzzaman; K. Y. S., Willison; M. C., Ong (Universiti Putra Malaysia Press, 2006)
14 cm cores sediments from the Paka River were analyzed for Mn, Cu, Zn, Pb and Th using the inductively coupled plasma mass spectrometer (ICP-MS). Generally, the concentrations of all elements decreased with depth and have significantly higher concentration at the surface depth of the core. The concentration of Mn and Cu have average value of 151.1 ± 59.1 mg/g dry weights and 29.2 ± 6.9 mg/g dry weights, while Zn and Pb averaged at 72.5 ± 15.5 mg/g dry weights and 54.9 ± 2.5 mg/g dry weights, respectively. Th were slightly varied widely and ranged from 0.6 mg/g dry weights to 1.4 mg/g dry weights. In this study, only Mn and Th have enrichment factor (EF) values close to unity and may therefore be considered to be predominantly terrigenous in origin. On the contrary, the higher EF values found for Cu, Zn and Pb indicate that these metals might have some influenced from the anthropogenic input